Pengaruh Current Ratio, Total Asset Turnover, Debt to Equity Ratio, & Return on Asset terhadap Nilai Perusahaan (Perusahaan Emiten Nikel Yang Terdaftar Di Bei Tahun 2020 - 2022) - Paulangan, Novia Saso; Wafa, Zaenal (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the effect of Current Ratio on Company Value in Nickel Issuer Companies for the 2020-2022 Period, to determine the effect of Total Asset Turnover on Company Value in Nickel Issuer Companies for the 2020-2022 Period, to determine the effect of Debt to Equity Ratio on Company Value in Nickel Issuer Companies for the 2020-2022 Period, and to determine the effect of Return on Asset on Company Value in Nickel Issuer Companies for the 2020-2022 Period. The research is associative causality with a quantitative approach, which aims to determine the cause and effect relationship between variables. Based on this study, it is concluded that Current Ratio has a significant positive effect on company value. Total Asset Turnover has a positive and significant effect on company value. Debt to Equity Ratio shows a negative effect on company value, but the results are not statistically significant. Return on Assets has a significant negative effect on company value.